How to be a good clerk on the clinical teaching team: a scoping review - Lively, Jordan; Gasim, Majid; Liu, Qingfan; Lingard, Lorelei (Canadian Medical Education Journal, 2024)
Background: As medical institutions shift towards Competency Based Education, more effort is being directed towards understanding how healthcare teams' function competently. While many have studied the competencies required to be a successful clerk, few have examined this question within the context of team function and integration. Our primary objective is to identify how medical clerks successfully integrate and contribute to clinical teaching teams. Methods: We performed a scoping review of the literature using the Ovid MEDLINE database. Data was extracted and thematically analysed in accordance with Arksey and O'Malley's (2005) approach to descriptive analysis. Results: Out of 1368 papers returned by our search, 12 studies were included in this review. Seven main themes were identified amongst the included studies: (1) Communication (2) Taking Responsibility and Appropriate Autonomy (3) Humility and Knowing When to Ask for Help (4) Identity as a Team Member, (5) Self-Efficacy (6) Rapport and Relationship Building (7) Patient Advocacy Conclusion: Analysis of these themes revealed four major findings: (i) The importance of documentation skills and communication towards team contribution (ii) The important connection between professional identity development and self-efficacy (iii) The impact of rapport on the reciprocity of trust between team members (iv) The role of clerks as patient advocates is poorly understood. This review also illustrates that there is a relative dearth of literature in this area. Future studies are needed to develop clear guidance on how clerks should perform these competencies in the context of team function and integration.